A new high-capacity metal ion-complexing gel containing cyclen ligands. Issue 28 (1st March 2016) - Dolan, Ciarán; Drouet, Fleur; Ware, David C.; Brothers, Penelope J.; Jin, Jianyong; Brimble, Margaret A.; Williams, David E.
Abstract : "Hairy" nano-scale objects cross-linked into a high-capacity metal-binding hydrogel. Abstract : We describe a new polymeric hydrogel that binds divalent metal ions with large binding constants and capacity. A new acrylate monomer with the pendant cyclen, tri- tert -butyl-10-(2-(2-(2-(methacryloyloxy)ethoxy)ethoxy)-2-oxoethyl)-1, 4, 7, 10-tetraazacyclododecane-1, 4, 7-tricarboxylate, was polymerised by RAFT to a roughly spherical 5–9 unit oligomer bearing a carboxylate-functionalised end-group. This was de-protected and coupled to an amine dendrimer then crosslinked into a nylon-type hydrogel capable of absorbing more than 10 wt% copper ions.